COMPARATIVE STUDY OF ELDERBERRY PHYTOAGGLUTININS AND ANTI-O HETEROIMMUNE SERA (International journal of medical sciences, 2025)
Currently, in most forensic medical laboratories worldwide, only a separate portion of the examined object is used to perform a particular type of analysis. Blood or secretion stains, as well as human tissues discovered on various pieces of physical evidence, are often very small in size. In such cases, “conducting only genetic analyses of micro-objects is not always advisable, as a negative result leaves unresolved the question of whether it was caused by loss of material during sample preparation or by the fact that the examined object does not originate from a human”.